Synthesis and 1H, 13C and 15N NMR characterisation of substituted Pyrazolo[4, 3-c]quinolines and related compounds. Issue 22 (31st May 2018) - Black, Shannon L.; O'Connor, Patrick D.; Boyd, Maruta; Blaser, Adrian; Kendall, Jackie D.
Abstract: A wide range of novel and known alkyl substituted pyrazolo[4, 3- c ]quinolines and related compounds were synthesized. Some of these compounds can undergo tautomerism and differences have been noted in the structural assignments already published. For each of these compounds, a complete assignment was made using 1 H, 13 C and 15 N one- and two-dimensional NMR measurements, including NOESY, COSY, 1 H- 13 C HSQC and 1 H- 13 C HMBC. 1 H- 15 N HMBC NMR has proved crucial in determining the relevant tautomeric and protonated state of the compounds. Graphical abstract: Image 1